Quantification of local blood flow characteristics in microfluidic applications - Kaliviotis, Efstathios; Sherwood, J.M.; Dusting, J.; Balabani, Stavroula (My University, 2016)
Advances in microfluidic applications have made it possible to design microsystems in which various processes, including diagnostics and fundamental research in biofluids, can be performed. In the majority of the studies the effect of red blood cell aggregation in blood flow characteristics has not received much attention and the relationship between the local microstructure and local flow characteristics has not been investigated extensively. In this work local velocity, local aggregation and local hematocrit of human red blood cells (RBC) have been simultaneously, resolved and quantified in a microchannel. The experimental system involved simple brightfield microscopy, a pressure driven microfluidic system, and RBCs suspended in Dextran and phosphate buffer saline solutions to control the aggregation intensity. Local aggregation characteristics were investigated at bulk and local levels using statistical and edge-detection image processing techniques. Aggregation intensity was found to strongly correlate with local variations in velocity in both the central and wall regions. The results suggest a combined effect of haematocrit and velocity distributions on local aggregation characteristics and showed that using multiple methods for aggregation quantification, could help towards a robust characterisation of the structural properties of the fluid
Keywords: Blood flow; Image processing techniques; Micro-PIV; Red blood cell aggregation